Beam Calibration of Radio Telescopes with Drones. (4th January 2016) - Chang, Chihway; Monstein, Christian; Refregier, Alexandre; Amara, Adam; Glauser, Adrian; Casura, Sarah
Abstract: We present a multifrequency far-field beam map for the 5-m dish telescope at the Bleien Observatory measured using a commercially available drone. We describe the hexacopter drone used in this experiment, the design of the flight pattern, and the data analysis scheme. This is the first application of this calibration method to a single-dish radio telescope in the far-field. The high signal-to-noise ratio data allows us to characterize the beam pattern with high accuracy out to at least the fourth side-lobe. The resulting two-dimensional beam pattern is compared with that derived from a more traditional calibration approach using an astronomical calibration source. We discuss the advantages of this method compared to other beam calibration methods. Our results show that this drone-based technique is very promising for ongoing and future radio experiments, where the knowledge of the beam pattern is key to obtaining high-accuracy cosmological and astronomical measurements.